Association between ADAMTS‐4 gene polymorphism and lumbar disc degeneration in Chinese Han population. Issue 5 (23rd November 2015) - Liu, Sen; Wu, Nan; Liu, Jiaqi; Liu, Hao; Su, Xinlin; Liu, Zhenlei; Zuo, Yuzhi; Chen, Weisheng; Liu, Gang; Chen, Yixin; Ming, Yue; Yuan, Tangmi; et al.
ABSTRACT: Low back pain (LBP) is a common health problem and many LBP are caused by lumbar disc degeneration (LDD). ADAMTS‐4 (a disintegrin and metalloprotease with thrombospondin motifs‐4), also known as aggrecanse‐1, plays a core role in degeneration of extracellular matrix in LDD. To investigate the association between ADAMTS‐4 genetic polymorphism and LDD, we genotyped SNPs in and around ADAMTS‐4 . We recruited 482 sporadic cases of LDD and 496 healthy controls from Chinese Han population. Five SNPs were selected and phenotyped by the Sequenom MassARRAY system. Allelic, genotypic, and haplotypic association was performed. Rs4233367 (c.1877 C>T), which located in exon of ADAMTS‐4 showed significant association with LDD. The T allele conferred a lower risk of LDD with an OR of 0.69 and TT genotype is at nearly one‐fifth of the risk compared to CC genotype. Other tested SNPs didn't show significant difference between the case and control groups. The SNP rs4233367 in the exon of ADAMTS‐4 gene may be associated with lumbar disc degeneration. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:860–864, 2016.